Interaction of Hot Work Climate on Physiological Responses of Apron Employees at Sultan Hasanuddin Airport, Makassar - Nurul Mawaddah Syafitri; Yulianah Rahmadani; Jumhur Salam; M. Anas (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: The apron area of an airport is a high-heat work environment that poses significant physiological stress to workers. Excessive heat exposure can lead to heat strain and health risks. This study aimed to analyze the interaction between hot work climate and physiological responses among apron employees at Sultan Hasanuddin Airport, Makassar. Methods: This was a cross-sectional study with an analytic-descriptive approach involving 67 purposively selected respondents from PT. Gapura Angkasa. The independent variable was the hot work climate measured by WBGT index (ISBB), and the dependent variables were heart rate and oxygen saturation before and after work. Data were analyzed using paired samples t-test with a significance level of p < 0.05. Results: The average WBGT value was 29.9°C, exceeding the recommended threshold. A significant increase in heart rate (p = 0.000) and a significant decrease in oxygen saturation (p = 0.000) were found after work. Most workers had long working hours (>40 hours/week) and long tenure, increasing their heat exposure risk. Conclusion: Hot work climate significantly affects the physiological responses of apron workers, as indicated by increased heart rate and decreased oxygen saturation. Risk control and regular physiological monitoring are essential to safeguard workers’ health and safety.